HUBUNGAN PENILAIAN KINERJA DAN PENGEMBANGAN KARIER DENGAN MOTIVASI KERJA PARA KARYAWAN DI YAYASAN MASJID AL-IKHLAS (YMAI) - Fathudin Ali (MANAGERE : Indonesian Journal of Educational Management, 2021)
The progress of a company or foundation is dependent on the productivity of its employees. If the productivity of the employees is high, the company/foundation will be easier to move forward. However, the motivation to have high productivity is a problem that is quite faced by management / leadership, because it is hoped that motivation will arise in employees, not because of coercion or threats. So for that, efforts are made to encourage the creation of self-motivation. Among them is an assessment of work performance and then accompanied by career and position development. The purpose of this study was to determine the extent of the relationship between performance and career development with work motivation of employees at Masjid Al-Ikhlas Foundation (YMAI), in particular, apart from being a requirement for completing the task of completing the International Institute. In this study, the authors used a questionnaire method, which was distributed randomly to employees in the YMAI work environment, which was then collected using the SPSS system. Finally the author came to the conclusion that there is a positive relationship between performance and career development at YMAI.